2014
DOI: 10.4103/1463-1741.132078
|View full text |Cite
|
Sign up to set email alerts
|

Relation of distortion product otoacoustic emission and tinnitus in normal hearing patients: A pilot study

Abstract: It was observed that the amplitudes of DPOAE were significantly lower in tinnitus patients than that of persons without complaint of tinnitus, at a frequency of 1281-1560, 5120-6250, 7243-8837 Hz, which imply that decrease of DPOAEs amplitudes may be related to the presence of tinnitus. It can be concluded that there is association between tinnitus and reduced OHC activity which indicate the OHC of cochlea are involved in the generation of tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…These results suggest that OHC loss may be a primary initiator in a series of events leading to tinnitus. Evidence based on clinical cases corroborates this hypothesis because patients suffering from tinnitus exhibit significantly lower amplitudes of otoacoustic emissions (generating from OHCs) than do persons without tinnitus [ 39 ]. Thus, it is assumed that reduced OHC activity is related to the generation of tinnitus.…”
Section: Partial Lesions Of the Cochleamentioning
confidence: 99%
“…These results suggest that OHC loss may be a primary initiator in a series of events leading to tinnitus. Evidence based on clinical cases corroborates this hypothesis because patients suffering from tinnitus exhibit significantly lower amplitudes of otoacoustic emissions (generating from OHCs) than do persons without tinnitus [ 39 ]. Thus, it is assumed that reduced OHC activity is related to the generation of tinnitus.…”
Section: Partial Lesions Of the Cochleamentioning
confidence: 99%
“…A foundation of modification in spontaneous activity within the auditory system could be an injury or abnormal task at any level, from the cochlea to the highest levels of the auditory system [ 3 ]. It had been also founded that there is an association between tinnitus and reduced outer hair cells activity which indicate the outer hair cells of cochlea are involved in the generation of tinnitus [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with tinnitus and normal hearing constitute an uncommon group and there is rare literature on tinnitus cases with normal hearing [ 4 ]. On the other hand there are many literature discussed tinnitus in patients with SNHL, like Sermin Kibar et al whom stated that “it was observed that simultaneously administration of vitamin B12 during noise had no protective effect on permanent threshold shift ” [ 23 ].…”
Section: Introductionmentioning
confidence: 99%